MULTICENTRYCZNOŚĆ SYSTEMU PRAWA POLSKIEGO A DZIAŁALNOŚĆ ORZECZNICZA EUROPEJSKIEGO TRYBUNAŁU SPRAWIEDLIWOŚCI I EUROPEJSKIEGO TRYBUNAŁU PRAW CZŁOWIEKA - Kalisz, Anna (Wydział Prawa i Administracji UAM, 2007)
The paper is an attempt to describe the way the phenomenon of multicentrism (in its external aspect) affects the process of the application of law. The paper shows the co-existence relations between the Polish legal system, Community law and the system of European Convention for the Protection of Human Rights, as well as their impact on the adjudication process. The conclusions drawn in the paper are based mainly on the jurisdiction of the European Court of Justice and the European Court of Human Rights.
MULTICENTRISM OF THE POLISH LEGAL SYSTEM AND THE JURISDICTION OF THE ECJ AND THE ECHR